Developing a pan-European technical standard for a comprehensive high-quality lung cancer computed tomography screening programme: an ERS technical standard - Baldwin, David; O'Dowd, Emma L.; Tietzova, Ilona; Kerpel-Fronius, Anna; Heuvelmans, Marjolein A.; Snoeckx, Annemiek; Ashraf, Haseem; Kauczor, Hans-Ulrich; Nagavci, Blin; Oudkerk, Matthijs; Putora, Paul Martin; Ryzman, Witold; et al. (The European respiratory journal, 2023)
Background Screening for lung cancer with low radiation dose computed tomography (LDCT) has a strong evidence base. The European Council adopted a recommendation in November 2022 that lung cancer screening (LCS) be implemented using a stepwise approach. The imperative now is to ensure that implementation follows an evidence-based process that delivers clinical and cost-effectiveness. This European Respiratory Society (ERS) Task Force was formed to provide a technical standard for a high-quality LCS programme. - Method A collaborative group was convened to include members of multiple European societies. Topics were identified during a scoping review and a systematic review of the literature was conducted. Full text was provided to members of the group for each topic. The final document was approved by all members and the ERS Scientific Advisory Committee. - Results Topics were identified representing key components of a screening programme. The actions on findings from the LDCT were not included as they are addressed by separate international guidelines (nodule management and clinical management of lung cancer) and by a linked ERS Task Force (incidental findings). Other than smoking cessation, other interventions that are not part of the core screening process were not included (e.g. pulmonary function measurement). 56 statements were produced and areas for further research identified. - Conclusions This European collaborative group has produced a technical standard that is a timely contribution to implementation of LCS. It will serve as a standard that can be used, as recommended by the European Council, to ensure a high-quality and effective programme. - Tweetable abstract ERSpublications - click to tweetLung cancer screening with LDCT has been recommended for stepwise implementation in Europe. A high-quality programme is essential for clinical and cost-effectiveness. This ERS technical standard defines the standards needed to achieve this. https://bit.ly/3KT2qOz